A geografia física de Kant : conhecimento do mundo, educação e cosmopolitismo - Serafim, Vicente Fagner Morais (2015)
Taught forty-nine times between 1756 and 1796, Kant's Physical Geography courses were conceived – together with those of Anthropology – as "propaedeutics" and "condition of possibility" for all forms of practical knowledge of the world, Among its most outstanding goals, "to civilize young students to become 'citizens of the world'." Kant understands by Physical Geography an empirical form of knowledge of spatial ordering and structures, producer of local and regional truths territorially derived from specific rules of citizenship. Until very recently neglected by scholars, the Physical Geography Courses were insufficiently explored and thus also the then visible implications that this empirical discipline has for Kant's conception of cosmopolitan ethics and education. It is necessary, therefore, to surpass the asystematic character of its composition, the prejudices therein manifested and the curiosities devoid of scientificity, and to systematically consider its general ideas and purposes, which have a direct repercussion on the Kantian understanding of pedagogy and morality.